PENGEMBANGAN MEDIA PERMAINAN PAPAN JELAJAH NUSANTARA (JENAR) DALAM MENGENAL KEBERAGAMAN BUDAYA INDONESIA UNTUK SISWA KELAS III SEKOLAH DASAR - Putri Isnandari; Raden Wisnu Wijaya Dewojati (CV. ADIBA AISHA AMIRA, 2026)
Pancasila Education learning in elementary schools still uses lecture methods and printed books, causing students to be less active, easily bored, and lack focus during the learning process. This condition has an impact on low student engagement in understanding the material on Indonesian cultural diversity. This study aims to develop the Jelajah Nusantara (Jenar) board game media as an interactive learning medium to introduce Indonesian cultural diversity to third-grade elementary school students. This study uses the Research and Development (R&D) method with the ADDIE model which includes the Analyze, Design, Development, Implementation, and Evaluation stages. The product developed is a pentagonal board game accompanied by pop-up and short materials about Indonesian cultural diversity from several provinces, question cards, challenge cards, chance cards, pawns, dice, and a game manual. The product was validated by media experts, material experts, and learning experts, then tested on teachers and 14 third-grade students of SD Negeri 2 Klirong. Data collection techniques used observation, interviews, questionnaires, and documentation. The results of the study indicate that the Jelajah Nusantara (Jenar) media obtained a